Severe major vessel injury during peadicle screw removal: a case report - Fu, ShengYu; Ju, Gang; Dai, Xiang; Li, Haijun; Huang, Aibing (Frontiers in Surgery, 2023)
Abstract Introduction: Pedicle screw fixation (PSF) has been the standard therapy for the treatment of various spinal diseases. Although complications are identified regularly, iatrogenic vascular injury is one of the rare but life-threatening complications. In this literature, we describe the first case of inferior vena cava (IVC) injury during pedicle screw removal. Case description: A 31-year-old man was treated by percutaneous pedicle screw fixation for an L1 compression fracture. After a year, the fracture healed well and hardware removal surgery was performed. During the procedure, the hardware on the right was removed unremarkably except for the L2 pedicle screw which slipped into the retroperitoneum because of the improper process. The CT angiogram revealed the screw had breached the anterior cortex of the L2 vertebral body and penetrated the IVC. After multidisciplinary cooperation, the defect of IVC was reconstructed and the L2 screw was removed from the posterior approach in the end. Result: The patient recovered well and was discharged after 3 weeks without further events. The removal of the contralateral implants was unremarkable at 7 months postoperatively. At the 3-year follow-up, the patient returned to his normal daily activity without any complaints. Conclusion: Although pedicle screw removal is a rather simple procedure, severe complications may have occurred from this procedure. Surgeons should keep vigilant to avoid the fatal complication noted in this case.